Escala de avaliação discente para educação superior a distância: proposição de uma metodologia - Santos, Roberta Souza (2023)
Public policies are essential for the well-being of the population, which is why they need to be evaluated in order to check that results are being achieved, in any area, such as education. In Brazil, higher education has been booming since the 2000s due to the development of various educational policies, such as distance learning. Within the theme of evaluation and the environment of distance education, the central aim of this study was to propose a student evaluation scale for distance education higher education courses (Avead). The specific objectives are: to carry out a literature review in order to identify existing student assessment models for distance learning courses; to construct the Avead student scale for distance learning higher education courses; to validate the Avead student scale for distance learning higher education courses; to propose a methodology for applying Avead at UFSM; to evaluate Avead in the UFSM environment and to propose a plan for applying the Avead scale to distance learning higher education courses at UFSM. The study's methodology is predominantly quantitative. Data was collected by means of a survey sent to all students enrolled in distance learning higher education courses via the UFSM Questionnaire system, with 337 valid responses. To design and build the Avead scale, inspiration was drawn from the evaluation models found in the literature and the premises of the Quality Standards for Distance Higher Education (RQESA). The scale was validated by experts and pre-tested to verify the proposed dimensions and items. Descriptive statistics and exploratory factor analysis (EFA) were used as analysis techniques. In addition, in order to propose a methodology for implementing the Avead scale in the context of the UFSM, the 5W2H technique was used (What? When? Where? Who? Why? How? and How Much?). After the estimations, the Avaed scale was validated with a set of 73 items divided into 11 dimensions: Teachers, Teacher Feedback, Tutors, Virtual Learning Environment, On-site Support Centre, Teaching Materials, On-site Meetings, Coordination Services, Distance Education Benefits, Student Self-Regulation and Satisfaction. The application methodology and implementation plan were then structured so that UFSM can structure the evaluation process for distance learning higher education courses. Finally, in a diagnostic assessment, it was observed that the students who answered the questionnaire were female (74.50%), married (55.80%), white (77.70%), had some kind of occupation (91.90%), had a gross monthly income of between one and four minimum wages (79.20%) and were aged between 30 and 49 (69.70%). It was also found that the students were from degree courses (63.20%) and specialisation courses (36.80%), and came from public schools (73.30%). As for the evaluation of the courses, in general they were well evaluated by the students, as most of the dimensions had averages above (4.00), meaning agreement with most of the items. By developing these tools and plans, the study seeks to ensure that the institution's management can use them to improve its decision-making.